An endonuclease with multiple cutting sites, Endo.SceI, initiates genetic recombination at its cutting site in yeast mitochondria. - Nakagawa, K (1992)
Endo.SceI is a mitochondrial sequence-specific endonuclease which has multiple cutting sites. In order to examine the possible role of Endo.SceI in homologous recombination, we analyzed the mode of recombination upon mating using antibiotic resistance markers on the mitochondrial genome. The segregation of a marker located very close to one of the Endo.SceI cutting sites showed a disparity (polarized segregation, i.e. gene conversion). This gene conversion depended on the presence of the functional Endo.SceI gene. In vivo cutting of mitochondrial DNA upon mating was detected at the cutting site in the antibiotic marker region, which also depended on the Endo.SceI activity. These results suggest that mitochondrial recombination is induced by cleavage of mitochondrial DNA by this sequence-specific endonuclease. This is the first demonstration that a sequence-specific endonuclease with multiple cutting sites induces genetic recombination.